Determination Method of the 4 Key Parameters of 3K-Ⅱ Planetary Transmission System - Fang Zhenjiang; Hua Qingsong (Jixie chuandong)
How to determine the number of tooth matching,center distance,modification coefficient and the tip diameter of the gear are four key techniques in the designing of 3K- Ⅱ planetary transmission mechanism. According to the particularity of 3K- Ⅱ planetary transmission mechanism,the new method of determining the tooth matching,center distance,shift coefficients and the tip diameter according to the transmission ratio is proposed. Based on the contrastive analysis of the key transmission quality indexes,the reasonability is verified and has a certain practical value of this method.